Hubungan Fungsi Manajerial Terhadap Pengendalian Mutu Dalam Industri Wisata: Sebuah Telaah Literatur - Muchammad Toyib; Suryanto Suryanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study explores the interplay between managerial functions and quality control in the tourism sector through a comprehensive literature review. It extensively covers the theoretical underpinnings of management definitions, managerial roles, quality control, and their contextual relevance within the tourism industry. Utilizing a two-stage literature review methodology involving databases like Google Scholar, ScienceDirect, and Scopus, nine pertinent journals were selected based on specific criteria. The findings underscore the pivotal role of service quality—cleanliness, staff friendliness, and food quality—in enhancing customer satisfaction, alongside the criticality of responsive customer feedback. Moreover, efficient management and adaptability to market dynamics emerge as cornerstones for sustaining tourism enterprises. The study synthesizes its results through case studies, emphasizing the importance of local stakeholder collaboration and a nuanced comprehension of customer preferences. It discusses practical implications, advocating for technology adoption and advanced analytics for competitiveness while acknowledging limitations in generalizing case study outcomes. Future research recommendations include exploring cultural influences on customer perceptions and devising predictive models for market trend forecasting. Keywords: Managerial Function, Quality Control, Tourism Industry, Customer Satisfaction, Market Adaptability